We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
155
2
avatar+164 

what is (f*g)(x)?

f(x)=x^2-5x+4

g(x)=x^3-1

what is the answer in standard form?

(f*g)(x)=____

 Apr 9, 2019
 #1
avatar+18754 
+1

(x^2-5x+4) * (x^3-1)  =     x^5 -5x^4 +4 x^3  - x^2 + 5x -4

 Apr 9, 2019
 #2
avatar+721 
+1

(f*g)(x)=f(x)*g(x)

(x^2-5x+4)(x^3-1)

x^5-x^2-5x^4+5x+4x^3-4

Now you can rearrange the terms.

 

You are very welcome!

:P

 Apr 9, 2019
edited by CoolStuffYT  Apr 9, 2019

4 Online Users

avatar